The Effects of Vitamin D Supplement on Prevention of Recurrence of Preeclampsia in Pregnant Women with a History of Preeclampsia - Behjat Sasan, Sanam (Obstet Gynecol Int, 2017)
INTRODUCTION: Preeclampsia is a pregnancy-specific syndrome. One of the hypotheses concerning the etiology of preeclampsia is vitamin D deficiency during pregnancy. METHOD AND MATERIALS: The present study is a randomized controlled clinical trial which aims to determine the effect of vitamin D supplement on reducing the probability of recurrent preeclampsia. 72 patients were placed in control group while 70 patients were randomized to the intervention group. The intervention group received a 50000 IU pearl vitamin D3 once every two weeks. The control group was administered placebo. Vitamin D or placebo was given until the 36th week of pregnancy. RESULTS: The patients in intervention group have significantly lower (P value = 0.036) probability of preeclampsia than patients in the control group. The risk of preeclampsia for the control group was 1.94 times higher than that for the intervention group (95% CI 1.02, 3.71). CONCLUSION: The intended intervention (i.e., prescription of vitamin D) has a protective effect against recurrent preeclampsia. Vitamin D supplementation therapy in pregnancy could help in reducing the incidence of gestational hypertension/preeclampsia. REGISTRATION: This study has been registered in Iranian Registry of Clinical Trials (IRCT) site with ID number IRCT2017010131695N1.